Why Human Wellbeing Must be an Educational Priority - Napier, David (Aktualitet - Litteratur, kultur og medier, 2009)
This paper by Professor Napier, Department of Anthropology, University College London, is based on a lecture he gave at the seminar, Literature, Welfare and Wellbeing. The Poetics of the Scandinavian Welfare State at Scandinavian Department, UCL, November 24th 2010. The seminar was supported by the UCL Grand Challenge of Human Wellbeing, the UCL School of European Languages, Culture and Society, the Department of Scandinavian Studies and the University of Southern Denmark Research Program in Welfare Narratives.